Pengaruh Current Ratio, Debt To Asset Ratio, Account Receivable Turnover, Return On Asset, Dan Dividen Per Share Terhadap Harga Saham Pada Perusahaan Manufaktur - Thomas Firdaus Hutahean; Kelvin Kelvin; Deli Prasasti Togatorop; Hotma Mentalita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of Current Ratio, Debt to Asset Ratio, Account Receivable Turnover, Return On Asset, and Dividend Per Share on stock prices in manufacturing companies. The population in this study is all manufacturing companies in the consumer goods sector and the use of the sample used is purposive sampling. The program used to process data is SPSS. Current Ratio has a negative and significant effect on stock price. Debt to Asset Ratio hasn’t a significant effect on stock price. Account Receivable Turnover hasn’t a significant effect on stock price. Return On Assets has a positive and significant effect on stock prices and Dividends Per Share have a negative and significant effect on stock prices. Current Ratio, Debt to Asset Ratio, Account Receivable Turnover, Return On Asset and Dividend Per Share have a significant effect on stock price. Keyword: Stock price, Current Ratio, Debt to Asset Ratio, Account Receivable Turnover, Return On Asset, Dividen per Share.